Stephen Hawking's universe : The cosmos explained - Filkin, David, (Basic books, 1997)
I began with far too little knowledge of such exotic ideas as white dwarfs, the Big Bang and black holes. I was even-what heresy- more than a litle suspicious that they might be figments of eccentric academy fantasy, rather than essential pieces in a scientific jigsaw. It does not help most of us to have faithin this jigsaw picture when it turns out to looklike nothing we have ever experienced. But I had an unquenchable desire to learn more, and a conviction that millionsof others wanted to understand these things too. All this quickly convinced me that there was still run for another approach. 1. Cosmology. 2. Hawking, S.W (Stephen W.) Brief history of time. I. litle QB981.F48 1997 523.1 dc21